Набутки чину святого Василія Великого на Правобережній Україні в галузі книговидавництва та їх нищення російським самодержавством наприкінці ХVІІІ – в першій половині ХІХ ст. - Шеретюк, Р.М. (Відділення релігієзнавства Інституту філософії ім. Г.С. Сковороди НАН України, 2010)
УстаттіРусланиШеретюкдосліджено книговидавничу діяльність
інтелектуального ядраУніатської церкви - Чину святогоВасиліяВеликого (ЧСВВ),
вплив на неї геополітичних трансформацій, пов’язаних з поділамиПольщі, а також
з’ясовано причини, механізми та наслідки поступової ліквідації василіанських
видавничих осередків.
Ключові слова: Уніатська церква, Чин святогоВасиліяВеликого, василіанські
типографії, богослужбова література, цензура, Почаївська василіанська друкарня. В статье Р.Шеретюк «Достояния Чина святого Василия Великого на
Правобережной Украине в книгоиздательской отрасли и их уничтожение
российским самодержавием в конце ХVIII – в первой половине ХIХ в.»
исследовано книгоиздательскую деятельность интеллектуального ядра Униатской
церкви – Чина святого Василия Великого (ЧСВВ), влияние на нее геополитических
трансформаций, связанных с разделами Польши, а также выяснены причины,
механизмы и последствия постепенной ликвидации василианских издательских
центров.
Ключевые слова: Униатская церковь, Чин святого Василия Великого,
василианские типографии, богослужебная литература, цензура, Почаевская
василианскаятипография. Ruslana Sheretyuk: The possessions of the rank of Saint Vasylyi the Great on the
right bank of Ukraine in the sphere of publishing and the destruction of them by
Russian autocracy at the and of 18th century – the first part of the 19th century. In
Ruslana Sheretyuk article «The possessions of the rank of Saint Vasylyi the Great on the right
bank of Ukraine in the sphere of publishing and the destruction of them by Russian autocracy
at the and of 18th century – the first part of the 19th century» examined the publishing house
activity of intellectual nucleus of the Uniat Church – the rank of Saint Vasylyi the Great
(RSVG) and the effect of geopolitical transformations which are connected with the allotment
of Poland on it; cleared up the reasons, the works and the results of gradual elimination of
Vasylian publishing centres.
Keywords: the Uniat Church, the rank of Saint Vasylyi the Great, Vasylian printing
houses, divine literature, censorship, Pochaiv-Vasylian publishing house.